High-surface-quality duplex stainless steel wire rod for cold heading and manufacturing method thereof
By controlling the Cr/Ni equivalent ratio and ferrite phase content, combined with the optimized rolling and solid solution treatment process, the defects of duplex stainless steel strips in production and downstream processing are solved, and high surface quality and good molding performance are achieved.
Patent Information
- Application Number
- CN202510380217.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-28
AI Technical Summary
The existing duplex stainless steel strips have defects such as rolling cracking, skin curling, and cracking during the production process, and are prone to cracking during downstream cold heading processing, affecting surface quality and molding performance.
By controlling the Cr/Ni equivalent ratio in the casting billet, the ferrite phase content is controlled at 40~60%, and the rough rolling speed is reduced during the rolling process. Combined with the solid solution treatment process, the heating and cooling process are optimized to ensure that the austenite structure is round and close to the island.
It achieves high surface quality of duplex stainless steel strips, avoids rolling cracking and cold heading cracking, improves the tensile strength, elongation and cross-section shrinkage of the finished product, and meets the standard performance requirements of the fastener.
Smart Images

Figure CN119876790A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of stainless steel production, and in particular relates to a duplex stainless steel wire rod with high surface quality for cold heading and a manufacturing method thereof. Background Art
[0002] In recent years, the use of duplex stainless steel has increased year by year. At present, the manufacturing process of duplex stainless steel wire rods produced by domestic manufacturers is generally: electric arc furnace - AOD furnace - LF furnace - continuous casting - hot rolling - offline solution. The duplex stainless steel wire rods produced by this manufacturing process have defects such as warping and cracks on the wire rod surface caused by rolling cracking due to the imbalance of the two-phase ratio and the uncoordinated deformation during the production process; in the use process of downstream customers, there are cold heading cracking problems caused by the large proportion of γ phase (austenite phase) and the difference in γ phase morphology.
[0003] In the production process of duplex stainless steel wire, due to the high γ phase content at the edge of the ingot, the ingot is subjected to uneven stress during rolling, resulting in defects such as warping and cracks in the finished product caused by rolling cracking. Therefore, regulating the structure of the ingot has become an indispensable link.
[0004] The downstream use of duplex stainless steel wire products is mainly cold heading fastener bolts. There are two common problems in the downstream use process: First, due to the large proportion of γ phase, the wire rod has high hardness, high yield strength, high forming difficulty, and high mold loss; second, due to the difference in γ phase morphology, the impact work of the wire rod decreases, and it is easy to crack after cold heading. Both problems of duplex stainless steel wire rod in the downstream cold heading process are related to the tissue content and morphology. Therefore, regulating the solid solution state wire rod structure of duplex stainless steel has become an indispensable link.
[0005] Chinese patent CN114932146A discloses "a method for rolling super duplex stainless steel wire", the round billet size of which is φ160mm. Compared with square billets, round billets do not have the problem of excessive temperature drop at the corners. The quality rate of the factory's duplex stainless steel wire has increased from 0% to 80%.
[0006] Chinese patent CN105821346A discloses "an economical duplex stainless steel wire and its manufacturing method". The chemical composition mass percentage of duplex stainless steel in the patent is: C: 0.01~0.05%, Si: 0.1~1.0%, Mn: 2.5~4.0%, Ni: 1.5~2.5%, Cr: 20.5~22.5%, Mo: 0.2~0.8%, N: 0.12~0.18%, W: 0.05~0.30%, P≤0.035%, S≤0.015%, and the balance is Fe and inevitable impurities; after the ingredients are prepared, the manufacturing method of the stainless steel is sequentially smelted, continuously cast, rolled, solution treated and pickled. The stainless steel wire can be used for processing and manufacturing stainless steel springs and other wire uses, and partially replaces 304 wire stainless steel.
[0007] Chinese patent CN115725811A discloses "a method for producing a second-generation duplex stainless steel wire". The chemical composition mass percentage of duplex stainless steel in the patent is: C≤0.03%, Mn: 1.30~1.60%, Si: 0.045~0.065%, P≤0.030%, Cr: 22.30~22.60%, Ni: 4.55~4.75%, Mo: 3.02~3.10%, and the balance is Fe and unavoidable impurities; the continuous casting billet is heated in a heating furnace and sent to a rolling mill to be rolled into a wire with a specification of φ5.5~23mm.
[0008] Chinese patent CN114904914A discloses "a rolling method for duplex stainless steel wire rods". The rolling method includes continuous casting billet preparation, heating, billet opening, intermediate billet heating, high-speed rolling and cooling, and further includes intermediate billet grinding. The invention optimizes the billet opening heating temperature and billet opening process pressure, optimizes the intermediate billet heating temperature and high-speed rolling process temperature, and the rolling process is equipped with induction heating equipment for online heating, which solves the problems of rolling cracking of duplex stainless steel, warping and cracking of the finished product surface, and the organization is uniform and has no precipitation.
[0009] The above patents involving duplex stainless steel wire rods mainly describe the composition design, shape change of ingot, continuous casting process, hot rolling process, heat treatment process, wire rod use, and quality improvement of duplex stainless steel wire rods, but do not involve a duplex stainless steel wire rod with high surface quality for cold heading and its manufacturing method. Summary of the invention
[0010] The object of the present invention is to provide a duplex stainless steel wire rod with high surface quality for cold heading and a manufacturing method thereof. The duplex stainless steel wire rod has a tensile strength of ≥620MPa, an elongation of ≥25%, a cross-sectional shrinkage of ≥50%, and a ferrite phase content of 40-60%, thereby avoiding cold heading cracking after downstream cold heading processing; the duplex stainless steel wire rod has no cracking during the rolling process, and has no defects such as warping and cracks on the wire rod surface, and has good surface quality; and the production cost is low, and the customer has good forming performance in the downstream cold heading processing, and the product meets the standard performance requirements of fasteners.
[0011] To achieve the above object, the technical solution of the present invention is: A duplex stainless steel wire rod with high surface quality for cold heading, the composition mass percentage of which is: C≤0.030%, Si: 0.40-0.60%, Mn: 4.05-4.40%, P≤0.040%, S≤0.0015%, Cr: 20.60-21.10%, Ni: 1.00-2.00%, Mo≤0.60%, V≤0.13%, Cu≤0.50%, N: 0.10-0.17%, Co≤0.15%, Ti≤0.030%, Nb≤0.030%, Al≤0.10%, and the balance includes Fe and other inevitable impurities; And at the same time meet: Cr / Ni equivalent ratio: 2.6~2.9; Cr equivalent = Cr + 1.5Mo + 2Si + 1.5Ti + 5.5Al + 5V; Ni equivalent = Ni + Co + 0.5Mn + 30C + 25N + 0.3Cu; The microstructure of the duplex stainless steel wire rod is austenite + ferrite, the ferrite phase content accounts for 40-60%, and the austenite structure is rounded and close to island shape; The duplex stainless steel wire rod has a tensile strength of ≥620 MPa, an elongation of ≥25%, and a cross-sectional shrinkage of ≥50%.
[0012] Furthermore, the balance of its composition is Fe and other inevitable impurities.
[0013] In the duplex stainless steel wire rod composition design of the present invention: C: C is an austenite-forming element. In duplex stainless steel, the presence of carbon not only promotes the formation of σ phase (harmful phase), but also reduces the corrosion resistance of stainless steel. In the downstream cold heading process, fasteners may cause cold heading cracking due to the presence of σ phase. In the present invention, the C content is controlled to be ≤0.030%.
[0014] Si: Si can be dissolved in ferrite and austenite. The lower the silicon content, the more rounded and island-like the austenite structure in the ingot is. However, too low a silicon content will increase the difficulty and cost of the preparation process. In the present invention, the Si content is controlled to be 0.40-0.60%.
[0015] Mn: Mn enhances the stability of the austenite phase structure and replaces nickel to a certain extent, but manganese deteriorates the corrosion resistance. In the present invention, the Mn content is controlled to be 4.05-4.40%.
[0016] P: P is a harmful element that easily increases the cold brittleness of steel. In the present invention, the P content is controlled to be ≤0.040%.
[0017] S: S is a harmful element that forms sulfide inclusions, which not only reduce the toughness and plasticity of steel, but also affect the corrosion resistance of dual-phase steel. When the S content in the dual-phase steel is ≤0.0015%, less ferrous sulfide is generated in the ingot, which can effectively reduce the harm of ferrous sulfide in the ingot to the grain boundary and reduce the rolling cracking ratio. In the present invention, the S content is controlled to be ≤0.0015%.
[0018] Cr: Cr is a ferrite-forming element. A higher Cr content can promote the formation of an intermetallic phase. In the present invention, the Cr content is controlled to be 20.60-21.10%.
[0019] Ni: Ni is an element that stabilizes austenite. Adding Ni delays the formation of harmful intermetallic phases in austenitic stainless steel. Ni metal has high cost. Considering the cost, the Ni content is controlled to be 1.00-2.00% in the present invention.
[0020] Mo: Mo is a ferrite-forming element and can improve corrosion resistance, but it also increases the tendency of stainless steel to form σ phase. In the present invention, the Mo content is controlled to be ≤0.60%.
[0021] Cu: The Cu element can enhance the corrosion resistance of stainless steel and improve the mechanical properties of duplex stainless steel. In the present invention, the Cu content is controlled to be ≤0.50%.
[0022] V: V can refine grains, improve toughness, and enhance the corrosion resistance of steel. In the present invention, the V content is controlled to be ≤0.13%.
[0023] N: N is a strong austenite forming element. It is the most effective solid solution strengthening element and low-cost alloying element. Increasing the N content in the structure can improve the mechanical properties of the material and reduce the precipitation temperature of harmful phases. The present invention controls the N content to 0.10-0.17%.
[0024] Co: Co can improve heat resistance and wear resistance, but too much content will deteriorate the toughness of the dual-phase steel. In the present invention, the Co content is controlled to be ≤0.15%.
[0025] Ti: The Ti element has the function of stabilizing carbides, but too much Ti content will deteriorate the toughness of the dual-phase steel. In the present invention, the Ti content is controlled to be ≤0.030%.
[0026] Nb: Nb element can refine grains, improve corrosion resistance, strengthen precipitation, and optimize welding performance, but the cost is high. In the present invention, the Nb content is controlled to be ≤0.030%.
[0027] Al: Too much Al content will easily form Al2O3 brittle inclusions in the molten steel. In the present invention, Al is controlled to be ≤0.10%.
[0028] Cr equivalent: Cr equivalent represents the ability of stainless steel to form ferrite structure; Ni equivalent: Ni equivalent represents the ability of stainless steel to form austenite structure.
[0029] The present invention has found that: When the α phase (ferrite phase) content in the ingot is 40~60%, the ratio of the two phases is balanced, which can effectively avoid stress concentration and rolling cracking caused by the large difference in the ratio of the two phases.
[0030] The traditional process relies on experience to adjust a single element to control the ferrite content in the ingot. The present invention studies and establishes a quantitative model to directly link the Cr / Ni equivalent ratio with the ferrite content of the ingot for the first time, thereby achieving precise control of the ferrite content in the duplex stainless steel ingot.
[0031] The quantitative relationship between the Cr / Ni equivalent ratio and the ferrite content was established through research experiments and regression analysis, and the following formula was obtained: Ferrite content in the ingot (%) = 66 × (Cr / Ni equivalent ratio) - 131.6: Combining the above research viewpoints and verified by production, when the Cr / Ni equivalent ratio in the dual-phase steel is 2.6~2.9, the α phase (ferrite phase) content in the resulting ingot structure is stabilized in the target range of 40~60%.
[0032] The method for manufacturing the duplex stainless steel wire rod with high surface quality for cold heading of the present invention comprises the following steps: 1) Smelting and casting According to the above composition, smelting and casting are performed into ingots with a cross-sectional size of 160×160~220×220mm; 2) Heating Control the preheating section temperature in the heating furnace to ≤1000℃, the heating section temperature to 1020~1100℃, the soaking section temperature to 1120~1170℃, and the furnace time to 2.0~4.0h; 3) Rolling Control the starting temperature of rough rolling to 1050~1120℃, the rough rolling speed to 0.8~1.2m / s, the rough rolling deformation to 75~80%, and the finishing rolling deformation to 25~85%; 4) Cooling The spinning temperature of the spinning machine is controlled to be 1000~1100℃, the heat preservation cover is opened, and the cooling fan is turned on, so that the cooling rate of the wire rod on the Stelmor roller is controlled to be ≥60℃ / min, the temperature of the wire rod inlet water cooling unit is 950~1020℃, and the temperature of the wire rod outlet water cooling unit is ≤200℃; 5) Solution treatment The solution temperature is 930~1080℃, and the time in the furnace is 1.5~3.0h, among which the low-temperature section temperature is 930~1020℃, the low-temperature section time is ≤1.0h, the high-temperature section temperature is 1040~1080℃, and the high-temperature section time is ≥1.0h; the temperature of the wire rod before entering the water is ≥1000℃, the cooling time of the wire rod is ≤15min, and the water outlet temperature of the wire rod is ≤60℃.
[0033] In the method for manufacturing duplex stainless steel wire rod of the present invention: In step 2), after high temperature Glibble tensile test curve and muffle furnace simulation, as Figure 1 As shown, the temperature of the soaking section of the heating furnace is controlled at 1120-1170°C, and the furnace time is 2.0-4.0 hours. Preferably, the furnace time is controlled at 2.0-2.5 hours. This can avoid coarse grains caused by long furnace time and obtain good high-temperature plasticity.
[0034] In step 3), the rough rolling speed is controlled at 0.8~1.2m / s, because the ferrite structure is easy to deform at high and low temperatures, while the austenite structure is difficult to recrystallize after the temperature is lowered, and the deformation difficulty increases. Therefore, a slow rough rolling speed is selected during rough rolling to promote austenite recrystallization, reduce the difference in deformation rate between ferrite and austenite structures, and improve the plasticity of the ingot.
[0035] The duplex stainless steel ingot of the present invention is subjected to rough rolling, intermediate rolling, pre-finishing rolling and finishing rolling to fix the wire size, wherein the finishing rolling deformation is 25-85% and the finishing rolling speed is 50-90 m / s.
[0036] In step 4), the spinning temperature of the spinning machine is controlled to be 1000-1100°C, the insulation cover is opened, the cooling fan is turned on, the cooling rate of the wire rod on the Stelmor roller is controlled to be ≥60°C / min, the temperature of the wire rod inlet water cooling unit is 950-1020°C, and the temperature of the wire rod outlet water cooling unit is ≤200°C.
[0037] In step 5), the temperature of the low temperature section is controlled to be 930~1020℃, and the temperature of the high temperature section is controlled to be 1040~1080℃. The solution treatment is designed with low temperature section and high temperature section. The low temperature section is designed to minimize the difference in mechanical properties of the coil; the high temperature section is designed to improve the toughness of duplex stainless steel to reduce the cracking ratio of cold heading bolts of downstream customers.
[0038] The design of the solid solution low-temperature section helps the heat conduction of the duplex stainless steel coil, avoiding uneven heating at different positions of the inner and outer rings of the coil due to excessively fast heating, large differences in the mechanical properties of the same coil, and uneven hardness problems when cold heading the coil for downstream customers.
[0039] The high temperature section temperature is controlled at 1040~1080℃, and the high temperature section time is ≥1.0h. The higher the solid solution temperature, the higher the impact energy performance. Figure 2 At the same time, the higher the solid solution temperature, the higher the temperature of the coil before entering the water. The coil is put into the water above the precipitation temperature of the σ phase, and the temperature of the coil before entering the water is controlled to be ≥1000℃ to avoid the precipitation of harmful phases of the σ phase.
[0040] For duplex stainless steel wire rod, the content and morphology of the γ phase (austenite phase) affect the mechanical properties of the wire rod. The higher the solid solution temperature, the lower the γ phase content, the lower the tensile strength and yield strength of the wire rod, and the higher the elongation; the higher the solid solution temperature, the more rounded the γ phase structure morphology is, the closer it is to an island shape, and the better the impact toughness of the material.
[0041] Wire rods with low tensile strength, yield strength and high impact energy are conducive to cold heading. Therefore, by studying the changes in the two-phase ratio of duplex stainless steel at different solid solution temperatures and conducting in-depth research on its structure, a duplex stainless steel wire rod structure control technology was proposed to solve the customer's problems of poor cold heading performance and cold heading cracking.
[0042] When the composition of the duplex stainless steel wire rod of the present invention requires the Cr / Ni equivalent ratio to be in the range of 2.6 to 2.9, the ferrite phase ratio of the duplex stainless steel wire rod is effectively regulated to be 40 to 60% by the solution treatment process of the present invention.
[0043] Compared with the prior art, the present invention is different in that: 1. Compared with Chinese patent CN114932146A, the process approach for improving surface quality of the present invention is different.
[0044] Chinese patent CN114932146A discloses "a method for rolling super duplex stainless steel wire". The patent uses round billets instead of square billets. The round billets are heat treated and then heated and rolled, and the quality rate is increased from 0% to 80%.
[0045] In the composition design of the present invention, the size of the billet is a common square billet of 160*160~220*220; in order to ensure that the content of the α phase (ferrite phase) of the billet is 40~60%, the Cr / Ni equivalent ratio is controlled to be 2.6~2.9.
[0046] In order to reduce the difference in deformation rate between ferrite structure and austenite structure during rough rolling, the present invention controls the rough rolling speed to 0.8-1.2 m / s.
[0047] In order to improve the impact energy and reduce the precipitation of the σ phase, the solution process of the present invention controls the temperature of the high temperature section of the solution furnace to 1040-1080°C, the high temperature section time is ≥1.0h, and the temperature before entering the water is ≥1000°C.
[0048] 2. Compared with Chinese patent CN105821346A, the product use, component design requirements, rolling process requirements, and solution process of the present invention are significantly different.
[0049] The existing Chinese patent CN105821346A discloses "an economical duplex stainless steel wire and its manufacturing method". After the ingredients are prepared, the stainless steel manufacturing method is smelted, continuously cast, rolled, solution treated and pickled in sequence. The chemical composition mass percentage of duplex stainless steel in the patent is: C: 0.01~0.05%, Si: 0.1~1.0%, Mn: 2.5~4.0%, Ni: 1.5~2.5%, Cr: 20.5~22.5%, Mo: 0.2~0.8%, N: 0.12~0.18%, W: 0.05~0.30%, P≤0.035%, S≤0.015%, and the balance is Fe and unavoidable impurities. In the rolling process of this patent, the continuous casting billet is placed in a heating furnace for heating at a temperature of 1100~1200℃ and a rolling temperature of 950~1150℃; in the solution treatment, the temperature of the offline solution treatment is 1000~1200℃.
[0050] In the composition design of the present invention, in order to ensure that the α phase content of the ingot is 40-60%, the Cr / Ni equivalent ratio is controlled to be 2.6-2.9. In order to reduce the difference in deformation rate between ferrite and austenite structures during rough rolling, the rough rolling speed is controlled to be 0.8-1.2 m / s. In order to increase the impact energy and reduce the precipitation of σ phase, the solid solution process of the present invention controls the temperature of the high temperature section of the solid solution furnace to be 1040-1080°C, the high temperature section time is ≥1.0h, and the temperature before entering the water is ≥1000°C.
[0051] 3. Compared with Chinese patent CN115725811A, the composition and heating furnace process of the present invention are different. In addition, the present invention has a solid solution process.
[0052] Chinese patent CN115725811A discloses "a method for producing second-generation duplex stainless steel wire", in which the chemical composition mass percentage of duplex stainless steel is: C≤0.03%, Mn: 1.30~1.60%, Si: 0.045~0.065%, P≤0.030%, Cr: 22.30~22.60%, Ni: 4.55~4.75%, Mo: 3.02~3.10%, and the balance is Fe and unavoidable impurities; in the rolling process of the patent, the continuous casting billet is heated by a heating furnace, the preheating section is heated to above 1000℃, the heating section is heated to 1130~1170℃, the holding time is ≤60min, the soaking section is heated to 1180~1210℃, the holding time is ≤60min, and it is sent to the rolling mill to be rolled into φ5.5~23mm specification wire.
[0053] In the composition design of the present invention, the Cr / Ni equivalent ratio is controlled to be 2.6-2.9 to ensure that the α phase content of the ingot is 40-60%. In order to reduce the difference in deformation rate between the ferrite structure and the austenite structure during rough rolling, the rough rolling speed is controlled to be 0.8-1.2 m / s. The solid solution process of the present invention has a solid solution process to increase the impact energy and reduce the precipitation of the σ phase.
[0054] 4. Compared with Chinese patent CN114904914A, the present invention clarifies the requirements of the component system, omits the blanking process, has a different heating furnace process, and has a solid solution process.
[0055] The existing Chinese patent CN114904914A discloses "a rolling method for duplex stainless steel wire rod". The rolling method includes continuous casting billet preparation, heating, billet opening, intermediate billet heating, high-speed wire rolling and cooling, and further includes intermediate billet grinding. After the intermediate billet is ground, the process temperature of the heating furnace is preheating section temperature: 800±20℃, time 60±20min; heating section: temperature 1000±20℃, time 40±5min; soaking section: 1230±10℃, time 30±5min.
[0056] In the composition design of the present invention, the Cr / Ni equivalent ratio is controlled to be 2.6-2.9 to ensure that the α phase content of the casting billet is 40-60%. The continuous casting billet of the present invention enters the heating furnace directly to roll the wire rod without the billet opening link; the present invention controls the rough rolling speed to be 0.8-1.2 m / s to reduce the difference in deformation rate between the ferrite structure and the austenite structure during rough rolling. The present invention has a solid solution process to increase the impact energy and reduce the precipitation of the σ phase.
[0057] Beneficial effects of the present invention: (1) The present invention constrains the alloy composition relationship Cr / Ni equivalent, and the α phase (ferrite phase) content in the ingot structure is 40-60%, and the ratio of the two phases is balanced, which can effectively reduce defects such as warping and cracking caused by rolling cracking, and improve the surface quality of the wire rod; (2) The blank of the present invention is heated at a lower temperature in the heating furnace, saving energy consumption; (3) The present invention reduces the warping and cracking defects caused by rolling cracking by controlling the rough rolling speed in the rolling process, thereby improving the surface quality of the wire rod; (4) By controlling the time and temperature in the solution furnace, the present invention can achieve a ferrite phase ratio of 40-60% in the duplex stainless steel wire rod, a rounded austenite structure, and a more island-like shape, thereby improving the impact energy. The customer has good forming performance in the downstream cold heading process, and the product meets the standard performance requirements of fasteners.
[0058] The stainless steel wire rod of the present invention has a tensile strength of ≥620MPa, an elongation of ≥25%, a cross-sectional shrinkage of ≥50%, and a ferrite phase content of 40-60%, thereby ensuring that the proportion of cold heading cracking after downstream cold heading processing is less than 0.1%, and the duplex stainless steel has no cracking during the rolling process; the wire rod surface has no defects such as warping and cracks, and the surface quality is good; the production cost is low and the performance is good, the customer has good forming performance in downstream cold heading processing, and the product meets the standard performance requirements of fasteners. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 Schematic diagram of high temperature surface shrinkage and high temperature strength of a billet in Example 1 of the present invention; Figure 2 Schematic diagram of the impact energy of the wire rod at different solid solution temperatures in Example 1 of the present invention; Figure 3 This is a cross-sectional microstructure photograph of the ingot in Example 1 of the present invention (α phase content 45.3%); Figure 4 This is a cross-sectional microstructure photograph of the ingot of Comparative Example 1 (α phase content 39.6%); Figure 5 This is a photo of the solid solution structure of the wire rod of Example 5 of the present invention (α phase content 51.1%); Figure 6 This is a photo of the solid solution structure of the wire of Comparative Example 5 (α phase content 39.8%). DETAILED DESCRIPTION
[0060] The present invention will be further described below in conjunction with the embodiments and drawings.
[0061] The composition indexes of the embodiments of the present invention and the comparative examples are shown in Table 1, and the balance includes Fe and other inevitable impurities; the manufacturing process of the embodiments of the present invention is shown in Table 2 and Table 3; the mechanical properties, α-phase content of the ingot, and α-phase content of the wire of the embodiments and the comparative examples are shown in Table 4.
[0062] The mechanical properties test of the material is carried out according to GB / T 228.1 "Tensile test of metallic materials Part 1: Room temperature test method".
[0063] The material structure test is carried out in accordance with GB / T 13305-2008 "Metallographic Determination of α Phase Area Content in Stainless Steel".
[0064] Compared with Examples 1 and 2, the Cr / Ni equivalent ratios of Examples 1 and 2 are 2.68 and 2.88, respectively, while the Cr / Ni equivalent ratios of Comparative Examples 1 and 2 are 2.49 and 2.48, respectively. The ferrite content in the ingots of Examples 1 and 2 is 45.3% and 58.5%, respectively, while the ferrite content in the ingots of Comparative Examples 1 and 2 is 39.6% and 38.1%, respectively. The ferrite content in the ingots of Examples 1 and 2 is higher than that in the ingots of Comparative Examples 1 and 2. The warping and cracking defect rates of Examples 1 and 2 are 1.0% and 1.5%, respectively, while the warping and cracking defect rates of Comparative Examples 1 and 2 are 12.3% and 14.9%, respectively. The α phase content in the ingot of Example 1 and the α phase content in the ingot of Comparative Example 1 are shown in Table 1. Figure 3 , Figure 4 .
[0065] Compared with Examples 3 and 4, the rough rolling speeds of Examples 3 and 4 are 0.91 m / s and 0.99 m / s, and the rough rolling speeds of Comparative Examples 3 and 4 are 1.30 m / s and 1.29 m / s. The warping and cracking defects of Examples 3 and 4 are 1.8% and 1.3%, and the warping and cracking defects of Comparative Examples 3 and 4 are 3.6% and 3.9%.
[0066] Compared with Examples 5 and 6, the high temperature section time of Examples 5 and 6 is 85min and 86min, and the high temperature section temperature of Examples 5 and 6 is 1075℃ and 1079℃; the high temperature section time of Comparative Examples 5 and 6 is 42min and 45min, and the high temperature section temperature of Comparative Examples 5 and 6 is 1021℃ and 1025℃. The α phase content of the wire rods of Examples 5 and 6 is 51.1% and 50.9%, and the α phase content of the wire rods of Comparative Examples 5 and 6 is 39.8% and 45.8%. The α phase content of the wire rod of Example 5 meets the proportion of 40-60%, and the austenite structure morphology is more rounded and close to island shape, see Figure 5 , Figure 6 .
[0067] In summary, the present invention controls the actual ferrite content in the ingot by controlling the Cr / Ni equivalent, reduces the rough rolling speed in the rolling process, reduces the warping and cracking defect rates, and obtains a duplex stainless steel wire rod with high surface quality. In addition, the present invention controls the furnace time and temperature through solid solution control, and adjusts the α phase ratio to close to the optimal ratio of 40-60%, while making the austenite morphology and austenite structure round and close to island shape, reducing the tensile strength and yield strength of the duplex steel, and improving the impact work of the material. The customer has good forming performance in the downstream cold heading process, and the product meets the standard performance requirements of fasteners.
[0068] The above contents are embodiments of the present invention and related analysis descriptions, rather than limiting the patent scope of the present invention. Any equivalent exchange made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
[0069]
[0070]
[0071]
[0072]
Claims
1. A duplex stainless steel wire rod with high surface quality for cold heading, characterized in that: The composition mass percentage is: C≤0.030%, Si: 0.40~0.60%, Mn: 4.05~4.40%, P≤0.040%, S≤0.0015%, Cr: 20.60~21.10%, Ni: 1.00~2.00%, Mo≤0.60%, V≤0.13%, Cu≤0.50%, N: 0.10~0.17%, Co≤0.15%, Ti≤0.030%, Nb≤0.030%, Al≤0.10%, and the balance includes Fe and other inevitable impurities; And at the same time meet: Cr / Ni equivalent ratio: 2.6~2.9; Cr equivalent = Cr + 1.5Mo + 2Si + 1.5Ti + 5.5Al + 5V; Ni equivalent = Ni + Co + 0.5Mn + 30C + 25N + 0.3Cu; The microstructure of the duplex stainless steel wire rod is austenite + ferrite, the ferrite phase content is 40-60%, and the austenite structure is rounded and close to island shape; The duplex stainless steel wire rod has a tensile strength of ≥620 MPa, an elongation of ≥25%, and a cross-sectional shrinkage of ≥50%.
2. The duplex stainless steel wire rod with high surface quality for cold heading according to claim 1, characterized in that: The remainder of the composition is Fe and other inevitable impurities.
3. The method for manufacturing a duplex stainless steel wire rod with high surface quality for cold heading according to claim 1 or 2, characterized in that: The following steps are involved: 1) Smelting and casting The composition of the duplex stainless steel wire rod according to claim 1 or 2 is smelted and cast into a casting billet with a cross-sectional size of 160×160~220×220mm; 2) Heating Control the preheating section temperature in the heating furnace to ≤1000℃, the heating section temperature to 1020~1100℃, the soaking section temperature to 1120~1170℃, and the furnace time to 2.0~4.0h; 3) Rolling Control the starting temperature of rough rolling to 1050~1120℃, the rough rolling speed to 0.8~1.2m / s, the rough rolling deformation to 75~80%, and the finishing rolling deformation to 25~85%; 4) Cooling The spinning temperature of the spinning machine is controlled to be 1000~1100℃, the heat preservation cover is opened, and the cooling fan is turned on, so that the cooling rate of the wire rod on the Stelmor roller is controlled to be ≥60℃ / min, the temperature of the wire rod inlet water cooling unit is 950~1020℃, and the temperature of the wire rod outlet water cooling unit is ≤200℃; 5) Solution treatment The solution temperature is 930~1080℃, and the time in the furnace is 1.5~3.0h, among which the low-temperature section temperature is 930~1020℃, the low-temperature section time is ≤1.0h, the high-temperature section temperature is 1040~1080℃, and the high-temperature section time is ≥1.0h; the temperature of the wire rod before entering the water is ≥1000℃, the cooling time of the wire rod is ≤15min, and the water outlet temperature of the wire rod is ≤60℃.
4. The manufacturing method according to claim 3, characterized in that: In step 2), the furnace time is 2.0~2.5h.
5. The manufacturing method according to claim 3, characterized in that: In step 3), the finishing rolling speed is 50~90m / s.
Citation Information
Patent Citations
Resource-saving duplex stainless steel wire rod and production method thereof
CN105821346A
Rolling method of duplex stainless steel wire rod
CN114904914A
Rolling method of super duplex stainless steel wire
CN114932146A
Production method of second-generation duplex stainless steel wire
CN115725811A
Economic duplex stainless steel with excellent cold forging performance and manufacturing method thereof
CN102719767A